The temporary bride : a memoir of love and food in Iran - Klinec, Jennifer (Twelve, 2017)
"Jennifer Klinec is fearless. In her thirties, she abandons her bland corporate job to launch a cooking school from her London apartment and travel the world in search of delicious recipes and obscure culinary traditions. Her journey takes her to Iran, where she seeks out a local woman to learn the secrets of Persian cuisine. Vahid is suspicious of the strange foreigner who turns up in his mother's kitchen. Unused to such a bold and independent woman, he is frustrated to find himself, the prized only son of the house, largely ignored for the first time. But when the two are thrown together on an unexpected adventure, they discover a mutual attraction that draws them irresistibly toward each other--but also pits them against harsh Iranian laws and customs, which soon threaten to tear the unlikely lovers apart. Getting under the skin of one of the most complex and fascinating nations on earth, THE TEMPORARY BRIDE is a soaring, intricately woven story of being loved, being fed, and struggling to belong,"--Amazon.com.